Homeland and exile in the novels of Rabai- Al- Madhoun - Rasheed V V (Post Graduate & Research Department of Arabic, Farook College (Autonomous) Kozhikode, 2023)
In this study, the researcher seeks to explore the themes of homeland and exile in Rabai’ al- Madhoun’s novels. Homeland and exile are interconnected topics; when an individual loses their homeland, they often experience a sense of exile. Exile can result from various circumstances such as war, occupation, or cultural displacement. The concept of "homeland" is complex and cannot be easily defined. The researcher divides the study into four chapters, with each chapter containing sub chapters and subsections focusing on specific themes, each concluding with a summary. The first chapter, titled "Homeland and Exile: An Analytical Study," comprises four sub chapters. The initial chapter discusses the concept of homeland, exploring its linguistic and terminological aspects, as well as themes of love and belonging to one's homeland as depicted in the Qur’an and Sunnah. The following sub chapter delves into theories of nationalism and patriotism, elucidating their distinctions. Additionally, the chapter explores exile, analyzing its linguistic and terminological dimensions, and various forms of exile. The second chapter, "The Development of the Palestinian Novel: An Overview," includes three sub chapters. The first sub chapter provides an overview of the evolution of the Palestinian novel, while the second sub chapter focuses on Rabai’ al-Madhoun's contributions to the development of Palestinian Arab literature. The third sub chapter discusses prominent Palestinian novelists. The third chapter is titled, "Rabai’ al-Madhoun: His Life and Writings," comprises four sub chapters. The initial sub chapter examines the literary persona of the author, followed by a discussion on his writings and a summary of his novels. Subsequent chapters delve into the place and time contexts depicted in Rabai’ al-Madhoun's works. The fourth chapter explores the themes of homeland and exile in Rabi’ al- Madhoun’s novels. This chapter is divided into five sub chapters. The first sub chapter examines narratives of homeland portrayed in the author's novels, while the second sub chapter explores issues of nationalism. The discussion concludes with an analysis of narratives depicting exile and the associated feelings within Rabai’ al-Madhoun’s narratives.
Thesis (Ph.D)- Farook College (Autonomous) Kozhikode, Post Graduate & Research Department of Arabic, 2023
Keywords: Homeland; Exile; Rabai’ al-Madhoun; Palestinian novel; Place and time contexts; Cultural displacement; Nationalism; Patriotism